Análise do Emprego de Sistemas de Drenagem Sustentável em Retroárea Portuária - Silva, Regiovilson Angelo da (2019)
The study analyzed the direct impact urbanization has on river basins and the flow of the basins; specifically due to the installation of a port and the retroarea. Compensatory drainage techniques were used for slowing flow growth: permeable floor VS a h